Enhanced electrocaloric effect in the Sm and Hf co-doped BaTiO3 ceramics. Issue 1 (1st January 2021) - Zhang, Boyang; Lou, Xiaojie; Zheng, Kun; Xie, Xuefan; Shi, Peng; Guo, Mengyao; Zhu, Xiaopei; Gao, Yangfei; Liu, Qida; Kang, Ruirui
Abstract: In this work, the electrocaloric (EC) effect was studied in the (100- x )BaHf0.2 Ti0.8 O3 - x Ba0.94 Sm0.04 TiO3 (BHT- x BST) ceramics fabricated by the conventional solid-reaction method. By tuning composition to their diffuse phase transition (DPT), invariant critical point (ICP) and first-order phase transition (FPT), the large electrocaloric response with a temperature change of ΔT  = 0.46 °C (at 64 °C) under 30 kV/cm and an electrocaloric strength of ΔT/ΔE  = 0.18 K mm/kV under 12 kV/cm were achieved in BHT-70BST. In addition, BHT-50BST shows a broad EC working temperature window from 28 °C to 68 °C because of its diffusion behavior near the ferroelectric-to-paraelectric phase transition and multiphase coexistence. The maximum ΔT of BHT-50BST is larger than that of BHT-40BST with only diffusion character but no multiphase coexistence. This work may provide a design strategy to enhance EC performance with a broad working temperature region in lead-free rare-earth doped BaTiO3 -based ceramics by combining the diffusion behavior, multiphase coexistence and heterovalent substitution.